2018
DOI: 10.1016/j.jsat.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessments for self-monitoring and counseling to optimize methamphetamine treatment and sexual risk reduction outcomes among gay and bisexual men

Abstract: This pilot study evaluated the use of smartphone ecological momentary assessments (EMA) for self-monitoring to optimize treatment outcomes among gay and bisexual men enrolled in an outpatient methamphetamine abuse treatment service program. Participants (N = 34) received EMA prompts five times daily to self-monitor their methamphetamine use, cravings, sexual risk behaviors, and associated triggers and affect throughout the 8-week treatment program. Participants were randomized into either a self-directed condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Out of 28 methamphetamine use interventions, 13 focused on reducing use among current users or among those at risk for use (Carrico et al, 2018;Carrico, Gómez, et al, 2015;Landovitz, Fletcher, Shoptaw, & Reback, 2015;Reback, Fletcher, Shoptaw, & Mansergh, 2015;Reback, Fletcher, Swendeman, & Metzner, 2019;Reback et al, 2012;Reback & Shoptaw, 2014;Shoptaw, Landovitz, & Reback, 2017;Shoptaw et al, 2008;Wu et al, 2011;Zhang, Shoptaw, Reback, Yadav, & Nyamathi, 2018;Zule et al, 2012); 10 interventions focused on individuals who met criteria for methamphetamine use disorder (Coffin et al, 2018;Colfax et al, 2011;Das et al, 2010;Landovitz et al, 2012;Lea et al, 2017;McElhiney et al, 2009;Mimiaga, Pantalone, et al, 2019;Reback et al, 2010;Reback, Rünger, Fletcher, & Swendeman, 2018;Shoptaw et al, 2005). The other five studies evaluated interventions for individuals who used methamphetamine, regardless of whether they met criteria for methamphetamine use disorder (Burgess et al, 2018;A.…”
Section: Methamphetaminementioning
confidence: 99%
“…Out of 28 methamphetamine use interventions, 13 focused on reducing use among current users or among those at risk for use (Carrico et al, 2018;Carrico, Gómez, et al, 2015;Landovitz, Fletcher, Shoptaw, & Reback, 2015;Reback, Fletcher, Shoptaw, & Mansergh, 2015;Reback, Fletcher, Swendeman, & Metzner, 2019;Reback et al, 2012;Reback & Shoptaw, 2014;Shoptaw, Landovitz, & Reback, 2017;Shoptaw et al, 2008;Wu et al, 2011;Zhang, Shoptaw, Reback, Yadav, & Nyamathi, 2018;Zule et al, 2012); 10 interventions focused on individuals who met criteria for methamphetamine use disorder (Coffin et al, 2018;Colfax et al, 2011;Das et al, 2010;Landovitz et al, 2012;Lea et al, 2017;McElhiney et al, 2009;Mimiaga, Pantalone, et al, 2019;Reback et al, 2010;Reback, Rünger, Fletcher, & Swendeman, 2018;Shoptaw et al, 2005). The other five studies evaluated interventions for individuals who used methamphetamine, regardless of whether they met criteria for methamphetamine use disorder (Burgess et al, 2018;A.…”
Section: Methamphetaminementioning
confidence: 99%
“…EMA has proven to be useful in the addiction field because substance use tends to be episodic and is associated with the individuals' mood and their environment ( Schulte et al., 2018 ; Shiffman et al., 2008 ). For example in a clinical setting, Reback et al. (2018) conducted a pilot study in which they recruited 34 treatment-seeking methamphetamine users who reported use in the previous 12 months.…”
Section: Effectiveness Of Digital Interventions For the Treatment Of mentioning
confidence: 99%
“…Of the 15 studies, 7 (47%) measured substance use status, including use of nicotine, alcohol, and other nonprescription drugs [9,11,24,27,29,33,34]. Of the 15 studies, 6 (40%) measured sexual behavior, especially, risky, unprotected sexual behavior defined by condomless sex or sex with partners who were of unknown HIV status [11,23,30,[32][33][34]. Of the 15 studies, 4 (27%) assessed the acceptability of EMAs implemented in an intervention by measuring response rates, completion rates, and study retention rates [9,25,26,31].…”
Section: Outcomes Of Interestmentioning
confidence: 99%